STRATEGI PENGEMBANGAN DAYA TARIK WISATA BUKIT HOLBUNG DI KABUPATEN SAMOSIR, SUMATERA UTARA - Sheila Vanessa, Wella Bella May; Khairi, Nurhafizhah; Elyanta, Marciella (Politeknik Pariwisata Medan, 2024)
This research aims to determine and describe tourist attractions and develop strategies for developing tourist attractions at Holbung Hill, Samosir Regency. This research uses qualitative methods with data collection techniques of observation, interviews, documentation studies and questionnaires. The results of the research show that tourist attractions according to Maryani's theory (1991) as a whole meet the criteria as a tourist attraction, which can be proven by the beautiful and stunning view of Holbung Hill (what to see), tourist attractions such as: camping, photography, pre-wedding and shooting locations (what to do), souvenirs processed by MSMEs in Hariara Pohan Village (what to buy), good accessibility including road conditions, ease of transportation and security to tourist attractions (what to arrive) and traditional house homestays that provide an experience The stay is different (what to stay) but there are still several things that need to be improved, namely the addition of new attractions and typical Holbung Hill souvenirs. The development of the Holbung Hill tourist attraction in Samosir Regency is a paragliding tourist attraction but has obstacles, namely limited skilled workers. The Holbung Hill tourist attraction in Samosir Regency, North Sumatra has strengths and opportunities that are greater than threats and weaknesses. Therefore, the development of Holbung Hill's tourist attraction focuses more on strengths and opportunities. A strategy that focuses on strengths and opportunities is a growth oriented strategy. Keywords: Holbung Hill, Tourist Attraction, Development